UV absorption cross-sections of phenol and naphthalene at temperatures up to 500 °C. (May 2015) - Grosch, H.; Sárossy, Z.; Egsgaard, H.; Fateev, A.
Abstract: Absorption cross-sections and their temperature dependency, especially in the UV spectral range, of organic compounds such as phenol and naphthalene are of great interest in atmospheric research and high temperature processes. Due to the challenges of producing premixed gases of known concentration, it is difficult to determine absorption cross-sections in experiments, especially at higher temperatures. In this paper, a gas flow of nitrogen with a stable but unknown concentration of phenol or naphthalene is produced, and their UV absorption spectra between 195 and 350 nm have been measured at higher resolution than before (0.019 nm) in a hot gas flow cell at temperatures of up to 500 °C/773 K. A Petersen column is used to sample the organic compounds in the gas mixture to determine their concentration by GC–MS. The absorption cross-sections are calculated with the use of the Lambert–Beer law. Consequently, the absorption cross-sections for phenol and naphthalene at room temperature, 423 K, 573 K and 773 K in the range of 195–360 nm are presented in this study. Abstract : Highlights: Phenol and naphthalene UV absorption cross-sections between 200 nm and 360 nm. Combination of absorption spectroscopy and GC–MS for absorption cross-section determination. Experimental measurements of temperature dependent absorption cross-sections up to 500 °C.